The double-edged sword of LMS in Basic Education Programmes: Teacher-Lived Experiences with KwaraLearn - Yusuf, Habibat Abubakar; Murtala, Abdulyaqin Tukur (IIUM Journal of Educational Studies, 2025)
This study explores the integration of KwaraLearn in basic schools to revolutionise teaching and administrative practices. A qualitative phenomenological approach was used for the study. Two research questions were raised to investigate the benefits and challenges faced by primary school teachers using KwaraLearn. Fourteen teachers were interviewed in person to elicit their views and lived experiences. Their responses were audio-taped and further validated with handwritten notes, and transcribed for thematic analysis. The research revealed that the platform offered significant advantages, including time optimisation through automated lesson tracking, a structured schedule that enhanced lesson organisation, and measurable academic progress with standardised assessment. However, these benefits are counterbalanced by persistent challenges, as mentioned by the teachers such as rushed teaching pace due to rigid digital timelines, resource deficits, particularly shortages of textbooks and supplementary materials for learners, and recurring technical issues that disrupted administrative tasks. While participants acknowledged KwaraLearn’s potential to enhance teaching, learning, and administrative tasks; concerns were raised on the technology-driven education platform and the classroom realities. This study concludes that the platform should be iterative and designed to prioritize teacher input and local realities to balance innovation with practicability.